Tailor-made ESP teaching materials for HEIs – two case studies - Marija Meršnik; Danijela Đorđević; Jelena Anđelković (Scripta Manent, 2023)
Commercially available teaching materials for Languages for Specific Purposes typically aim to cater to the needs of a wide range of students, even within a specific professional area. Therefore, when dealing with a more specialized purpose, as is the case with two Higher Education Institutions (HEIs) under review in this paper, additional time, resources, and effort are required to produce more tailored materials that suit the needs of specific target groups. This paper presents two case studies of ESP teaching materials design resulting in the creation of two tailor-made coursebooks used in two Serbian HEIs specializing in agriculture and food technology, and management, respectively. The paper outlines the materials writing process and compares the final products (i.e. the two ESP coursebooks) by encompassing various aspects, including course rationale and syllabi (such as learning outcomes, aims and objectives, students’ entry levels, syllabi framework types, etc.), approaches to needs analysis, content choice and sequencing, copyright and other issues, theoretical and methodological frameworks, the timeline and the steps in the process. Despite the differences in target groups, teaching content, learning outcome, established frameworks, etc., the two writing processes and their final products underwent similar steps and identified comparable limitations and areas of improvement. Both processes also share a key takeaway: tailor-made ESP coursebook writing process, though arduous and time-consuming, is an effort worth taking.